High microsatellite instability (MSI-H) is associated with distinct clinical and molecular characteristics and an improved survival in early Colon cancer (CC); real world data from the AIO molecular registry Colopredict Plus - Noepel-Duennebacke, Stefanie; Juette, Hendrik; Feder, Inke Sabine; Kluxen, Larissa; Basara, Nadezda; Hiller, Wolfgang; Herzog, Torsten; Klaassen-Mielke, Renate; Mueller, Lothar; Senkal, Metin; Engel, Lars; Teschendorf, Christian; Trenn, Guido; Verdoodt, Berlinda; Wolters, Heiner; Uhl, Waldemar; Reinacher-Schick, Anke; Tannapfel, Andrea (Zeitschrift für Gastroenterologie, 2020)
Colorectal cancer is one of the leading malignancies and still accounts for almost 25 000 deaths in Germany each year. Although there is accumulating data on the molecular basis, treatment and clinical outcome of patients within clinical trials evidence from the real-world setting is mostly lacking. We started the molecular registry trial Colopredict Plus in 2013 to collect clinical and molecular data from a real-world cohort of patients with early colon cancer stage II and III in 70 German colon cancer centers focusing on the prognostic impact of high microsatellite instability. In this interim report, we characterize a clinical cohort of 2615 patients, of whom 1787 tissue probes were analyzed. Microsatellite status was assessed using immunhistochemistry and fragment length analysis, with a concordance of 91.4 %. These established histopathological methods are sensitive and cost-effective. The median age was 72 years, significantly higher compared to clinical trial populations, with a median Charlson Comorbidity Index of 3. The stage-dependent incidence of microsatellite instability was 23.7 % and was associated with female gender, BRAF-mutation, UICC stage II and localization in the right colon. Survival calculated in disease free, relapse free and overall survival significantly differed between MSI-H and MSS, in favor of MSI-H patients. Multivariate age-adjusted analyses of relapse-free survival, disease-free survival, and overall survival highlighted microsatellite instability as a robust and positive prognostic marker for early colon cancer independent of age.
Keywords: microsatellite instability; colon cancer; real world data; BRAF; registry